Page 116 - مبادىء الاحصاء_Neatاولى سياحه
P. 116

‫‪=  X 2 −2X X +  X 2‬‬
               ‫‪n −1‬‬

‫‪X =  X ،،‬‬  ‫وحيث أن‪ X = nX :‬‬

        ‫‪n‬‬

            ‫كذلك فإن‪ X 2 = nX 2 :‬‬

                             ‫على ذلك‪:‬‬

‫‪S 2 = X 2 − 2XnX + nX 2‬‬
                ‫‪n −1‬‬

 ‫‪ X 2 − 2nX 2 + nX 2‬‬

‫=‬
            ‫‪n −1‬‬

 ‫‪ X 2 − nX 2‬‬

‫=‬
       ‫‪n −1‬‬

‫كما يمكن وضع المعادلة السابقة في الصورة التالية‪-:‬‬

                             ‫حيث أن ‪:‬‬

‫‪X = X‬‬      ‫= ‪( )،، X 2‬‬ ‫‪X2‬‬
                        ‫‪n2‬‬
        ‫‪n‬‬

                             ‫على ذلك‪-:‬‬

            ‫‪116‬‬
   111   112   113   114   115   116   117   118   119   120   121